CHARACTERIZATION OF A POROUS NICKEL-TITANIUM ALLOY PRODUCED WITH SELF-PROPAGATING HIGH-TEMPERATURE SYNTHESIS - Tosun, Gul; Kilic, Musa; Ozler, Latif; Tosun, Nihat (Inst Za Kovinske Materiale I in Tehnologie, 2018)
The porous NiTi shape-memory alloy (SMA) is a promising biomaterial due to its attractive mechanical property and proper biocompatibility. In this research, the effects of the production parameters on the porosity of the above SMA were investigated using self-propagating high-temperature synthesis (SHS). Powders containing 50.5 atomic percent of Ni and 49.5 atomic percent of Ti were blended for 24 h and cold pressed at pressures of (100, 150 and 200) MPa. After that, NiTi-alloy green compacts were synthesized with the SHS process at different preheating temperatures of (200, 250 and 300) degrees C, while some of these samples were sintered. The effects of the production parameters, namely, the heat treatment, pressure and preheating temperature on the microstructure and porosity were examined. Microhardness tests were done in order to evaluate the mechanical properties. In addition to NiTi, there were other secondary intermetallic compounds (NiTi2, Ni3Ti and Ni4Ti3) as the base phases of the microstructure. The porosity was changed depending on the process parameters. The porosities of the synthesized products were obtained in a range of 38.6-56 volume percent. It was observed that the preheating temperature had an important effect on the pore-size distribution of the NiTi product. The sintering heat treatment changed the distribution of the phases in the microstructure. The main phase of the porous NiTi alloy was the NiTi phase together with the Ni3Ti2 and Ni2Ti secondary phases.
Keywords: biomaterials; high-temperature synthesis (SHS); powder metallurgy; porosity; microstructure; hardness